Resolution of Multiple Certificates By The National Land Agency (BPN) of Pamekasan District In Prevention of Land Mafia - Rokhman; Iwan Permadi; Supriyadi (Faculty of Law, Merdeka University Surabaya, Indonesia, 2025)
Land mafia is still a serious threat in Indonesia, including in Pamekasan Regency, where the need for land is increasing rapidly. This study aims to examine the role of the National Land Agency (BPN) in resolving dual certificate disputes which are often the modus operandi of land mafia. The study uses a normative legal method with a descriptive analytical approach, as well as data collection through literature studies and legal documents. The results show that land mafia exploits weaknesses in land administration, especially in issuing fake documents and falsifying dual certificates. The Ministry of Agrarian Affairs and Spatial Planning/BPN has formed policies and an Anti-Land Mafia Task Force to prevent and eradicate this practice. However, the success of handling this problem requires cross-sector coordination and consistent law enforcement. In an effort to eradicate dual certificates from land mafia practices, the Ministry of ATR/BPN has made written regulations, namely Technical Instructions for the Prevention of Eradication of Land Mafia Number: 01/JUKNIS/D.VII/2018. In addition, the Ministry of ATR/BPN also formed a Land Mafia Task Force Team in order to eradicate land mafia practices that have the potential to cause double certificates based on bad faith. This study is expected to provide input for improving land law policies, in order to ensure justice and legal certainty for the community.